Integridad pública y rendición de cuentas en la administración pública del GAD Parroquial Rural Bachillero período 2022-2024 - Ganchozo Cedeño, Yaritza Lisbeth (2025)
The present research aimed to analyze public integrity and accountability as public administration mechanisms for the management of the Bachillero Rural Parish GAD during the 2022–2024 period. Various activities were carried out across different phases to fulfill the specific objectives. First, a bibliographic review and analysis of national and local legislation related to the study variables were conducted, employing the deductive method, the analytical-synthetic approach, and bibliographic research. Subsequently, an interview was designed and applied to the institution’s president, along with a structured survey administered to the citizens of the Bachillero parish. The survey was developed based on the dimensions of the study variables, using the Likert scale as a measurement tool, and the results were analyzed accordingly. Based on the findings, an improvement plan was designed that includes specific strategies to address the identified areas. The research revealed a lack of public access to information regarding decisions and projects executed by the local government, limited citizen participation in meetings or events intended for civic engagement, and low awareness of the existence and effectiveness of internal mechanisms for monitoring and controlling public resource use. In conclusion, this study highlights the importance of strengthening transparency and citizen participation to enhance local public management.